The Efforts to Improve Students - Yoni Marlius; Bambang Bambang; Metsra Wirman (Universitas Islam Negeri Palangka Raya, 2021)
Maharah al-kalam or Arabic speaking skills have an essential role for students, especially students who take Arabic courses. Ironically, maharah al-kalam's urgency is not always accompanied by the efforts to actualize maharah al-kalam's activeness. Although several institutions have attempted to realize these efforts, it has not been exposed extensively so that other institutions cannot adopt the methods or technics used by these institutions. Therefore, this study aimed to explore the efforts to improve maharah al-kalam, one of the Muhammadiyah universities implemented in Indonesia, through the language environment activation. This study used a qualitative-phenomenology approach. The data collection techniques used were observation, interview, and documentation study. This study indicated three patterns of the Arabic language environment activation implemented in the tertiary institution: the display of pamphlets with an instruction to speak Arabic, vocabulary boards, and Arabic today. This study's findings also emphasized the importance of cooperation among the institution managers, lecturers, and students to comply with the mutually agreed rules. Without collaboration and commitment between the parties, the desired results will not be achieved.